Sustained release local anesthetics for pain management: relevance and formulation approaches - Getachew, Melese; Tesfaye, Hana; Yihunie, Wubetu; Ayenew, Tesfahun; Alemu, Sintayehu; Dagnew, Ephrem Mebratu; Biyazin, Yalemgeta; Abebe, Dehnnet; Degefu, Natanim; Abebaw, Abtie (Frontiers in Pain Research, 2024)
This review attempted to ascertain the rationale for the formulation of sustained-release local anesthetics and summarize the various formulation approaches designed to date to achieve sustained and localized local analgesic effects. The incidence of pain, which is the concern of patients as well as health care professionals, is increasing due to accidents, surgical procedures, and other diseases. Local anesthetics can be used for the management of moderate to severe acute and chronic pain. They also allow regional analgesia, in situations where the cause and source of the pain are limited to a particular site or region, without the need for loss of consciousness or systemic administration of other analgesics thereby decreasing the risk of potential toxicities. Though they have an interesting antipain efficacy, the short duration of action of local anesthetics makes the need for their multiple injections or opioid adjuvants mandatory. To overcome this problem, different formulations are being designed that help achieve prolonged analgesia with a single dose of administration. Combination with adjuvants, liposomal formulations, lipid-based nanoparticles, thermo-responsive nanogels, microspheres, microcapsules, complexation with multivalent counterions and HP-β-CD, lipid-based nanoparticles, and bio-adhesive films, and polymeric matrices are among the approaches. Further safety studies are required to ensure the safe and effective utilization of sustained-release local anesthetics. Moreover, the release kinetics of the various formulations should be adequately established.